1995
DOI: 10.1152/jappl.1995.79.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of arousal from sleep on cardiac autonomic outflow in the absence of breathing in dogs

Abstract: To determine the immediate effects of arousal from non-rapid-eye-movement (non-REM) sleep on cardiac sympathetic and parasympathetic activities, six dogs were studied breathing through an endotracheal tube inserted into a chronic tracheostomy. Mean heart rates (HRs) during non-REM sleep were compared with 1) awake periods immediately after spontaneous arousals (ARs) and 2) later periods of stable relaxed wakefulness (RW). During spontaneous breathing, HR increased after AR (mean = 31.0%; P < 0.001) and in RW (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 0 publications
4
88
1
5
Order By: Relevance
“…Although bronchi are innervated by parasympathetic rather than sympathetic nerves in mammals [16,18], circulating adrenalin is a potent bronchodilator in humans [17]. During apnoeic periods, parasympathetic tone is decreased [24] and repeated arousal stimuli are associated with increased sympathetic activity [25], which may also lead to bronchodilation. This imbalance between sympathetic and parasympathetic tone may last even during wakefulness [15,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although bronchi are innervated by parasympathetic rather than sympathetic nerves in mammals [16,18], circulating adrenalin is a potent bronchodilator in humans [17]. During apnoeic periods, parasympathetic tone is decreased [24] and repeated arousal stimuli are associated with increased sympathetic activity [25], which may also lead to bronchodilation. This imbalance between sympathetic and parasympathetic tone may last even during wakefulness [15,26].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Their underlying pathological mechanisms include recurrent intermittent hypoxemia and increased sympathetic activity, primarily at the termination of the apneic events. 8,9 In a previous study, 10 our group showed that OSAS is also associated with ED in a dose-related fashion. This association is very strong in patients with severe OSAS and weaker in patients with mild or moderate OSAS.…”
Section: Introductionmentioning
confidence: 86%
“…In dogs, spontaneous arousals from sleep were associated with acute rises in heart rate due to both sympathetic activation and parasympathetic withdrawal, and could be prevented by sympathetic block [40]. In pigs, arousals induced by tracheal obstruction during sleep were associated with increases in blood pressure, heart rate and coronary vascular resistance [41].…”
Section: Arousals and The Autonomic Nervous Systemmentioning
confidence: 99%